Power distance among leaders in tourism - Abdul Hamid, Nur Atiqah; Mokhtar, Nor Zainiyah Norita; Chung, Jaime/Ji-Hye (2017)
The purpose of this study is to explore the influence of power distance on leadership in tourism industry. This paper aimed to understand behaviours in leadership conducts and the aspects of power distance affecting these behaviours. The findings of the paper depict that where power distance is concerned, a leader in the tourism industry needs to be someone who is evasive and a win/win problem solver.